2018
DOI: 10.1097/md.0000000000010882
|View full text |Cite
|
Sign up to set email alerts
|

Expression profile of circular RNAs in infantile hemangioma detected by RNA-Seq

Abstract: We found that of the 9811 identified circRNAs, 249 candidates were differentially expressed, including 124 upregulated and 125 downregulated circRNAs in the IH group compared with the matched normal skin control group. A set of differentially expressed circRNAs (in particular, hsa_circRNA001885 and hsa_circRNA006612 expression) were confirmed using qRT-PCR. Gene ontology and pathway analysis revealed that compared to matched normal skin tissues, many processes that were over-represented in IH group were relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…For example, Yuan et al [ 35 ] found that circAP2A2 can promote the proliferation and invasion of IH by regulating the miR-382-5p/VEGFA axis. Through RNA-Seq research, Li et al [ 36 ] found that among 9811 identified circRNAs, 249 candidate genes were differentially expressed, including 124 upregulated and 125 downregulated circRNAs. The study of these circRNAs is of great value for the prevention and treatment of IH and explaining the mechanism of IH occurrence and development.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Yuan et al [ 35 ] found that circAP2A2 can promote the proliferation and invasion of IH by regulating the miR-382-5p/VEGFA axis. Through RNA-Seq research, Li et al [ 36 ] found that among 9811 identified circRNAs, 249 candidate genes were differentially expressed, including 124 upregulated and 125 downregulated circRNAs. The study of these circRNAs is of great value for the prevention and treatment of IH and explaining the mechanism of IH occurrence and development.…”
Section: Discussionmentioning
confidence: 99%
“…According to the manufacturer's instructions, Real-time PCR was performed using SYBR Green (TaKaRa Biotech, Dalian). The glyceraldehyde-3-phosphate dehydrogenase (GAPDH) gene was used as an internal control to normalize the expression level of circRNAs 74 . Three independent experiments were carried out on LCG and MCG skin samples.…”
Section: Identification Of Circrnas and Analysis Of Differentially Exmentioning
confidence: 99%
“…Among them, hsa_circ_100933 and hsa_circ_100709 were upregulated, and hsa_circ_104310 was downregulated. Similarly, Li et al [ 36 ] conducted a study on the proliferating capillary hemangioma and matching normal skin tissues, obtained from 3 children, and found 249 differentially expressed circRNAs (DE-circRNAs) via qRT-PCR. There were 124 upregulated and 125 downregulated circRNAs in the IH tissue.…”
Section: Circrna and Common Smts In Childrenmentioning
confidence: 99%